2016
DOI: 10.1038/nature17657
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination independent of E1 and E2 enzymes by bacterial effectors

Abstract: Signaling by ubiquitination regulates virtually every cellular process in eukaryotes. Covalent attachment of ubiquitin to a substrate is catalyzed by the E1, E2 and E3 three-enzyme cascade 1, which links the C terminus of ubiquitin via an isopeptide bond mostly to the ε-amino group of a lysine of the substrate. Given the essential roles of ubiquitination in the regulation of the immune system, it is not surprising that the ubiquitination network is a common target for diverse infectious agents 2. For example, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
444
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(470 citation statements)
references
References 40 publications
12
444
0
3
Order By: Relevance
“…130 Finally, a peculiar yet interesting study recently reported that SdeA, belonging to the SidE family effectors of L. pneumophila, is a novel all-in-one ubiquitin conjugation enzyme, which solely mediates the ubiquitination of many host Rab GTPases by virtue of a putative mono-ADPribosyltransferase motif. 131 Of note, this report not only demonstrates for the first time that ubiquitination can be catalyzed by bacterial effectors in the absence of E1 and E2 enzymes but also hints that ubiquitin can be activated by ADP ribosylation.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…130 Finally, a peculiar yet interesting study recently reported that SdeA, belonging to the SidE family effectors of L. pneumophila, is a novel all-in-one ubiquitin conjugation enzyme, which solely mediates the ubiquitination of many host Rab GTPases by virtue of a putative mono-ADPribosyltransferase motif. 131 Of note, this report not only demonstrates for the first time that ubiquitination can be catalyzed by bacterial effectors in the absence of E1 and E2 enzymes but also hints that ubiquitin can be activated by ADP ribosylation.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…The electronic and magnetic properties of graphene nanoribbons correlate closely with the structures of their edges, and are sensitive to even minute numbers of defects. Isolating a sufficient number of nanoribbons that have perfect zigzag edges to enable their magnetic characterization is extremely challenging, and so the data from such studies 6 are scarce and inconclusive. Experiments performed on single graphene layers prepared in situ under a high vacuum have revealed the formation of local electronic states at edges, but did not provide any evidence of magnetism 7 .…”
Section: F E R N a N D O Lu I S And E U G E N I O C O R O N A D Omentioning
confidence: 99%
“…So far, only a few SdeA substrates have been identified 6,8,9 ; these include the GTPase enzymes Rab and Rag, as well as the protein RTN4. From analysis of the ubiquitination sites in host proteins, Kalayil et al and Wang et al propose that the ligase enzyme specifically targets serine residues in disordered protein regions.…”
mentioning
confidence: 99%
See 2 more Smart Citations